Ipilimumab: A First-in-Class T-Cell Potentiator for Metastatic Melanoma - Bartosz Chmielowski (Journal of Skin Cancer)
Ipilimumab, a fully human anti-cytotoxic T-lymphocyte antigen-4 monoclonal antibody that potentiates antitumor T-cell responses, has demonstrated improved survival in previously treated and treatment-naïve patients with unresectable stage III/IV melanoma. Survival benefit has also been shown in diverse patient populations, including those with brain metastases. In 2011, ipilimumab (3 mg/kg every 3 weeks for 4 doses) was approved by the Food and Drug Administration for unresectable or metastatic melanoma. Ipilimumab can induce novel response patterns for which immune-related response criteria have been proposed. irAEs are common but are usually low grade; higher grades can be severe and life-threatening. irAEs are usually manageable using established guidelines emphasizing vigilance and prompt intervention. This agent provides an additional therapeutic option in metastatic melanoma, and guidelines for management of adverse events facilitate clinical implementation of this new agent.